Missing what's right under your nose: Failed appetitive and aversive audio-olfactory conditioning in humans - Menger, N.S.; Kotchoubey, B.; Ohla, K.; Pavlov, Y.G. (International journal of psychophysiology, 2025)
The comparison of physiological mechanisms underlying appetitive and aversive conditioning is often challenging due to the involvement of stimuli from different modalities with potentially disparate effective mechanisms (e.g., pain stimuli versus monetary rewards). The olfactory system offers a unique opportunity to examine both types of conditioning in humans, as isointense odors can serve as comparably pleasant and unpleasant stimuli. To study physiological and behavioral responses during appetitive and aversive learning, we employed odors as unconditioned stimuli (US) in a within-subjects design, measuring various conditioned physiological responses including skin conductance, heart rate, pulse wave amplitude, respiration, fear-potentiated startle, postauricular reflex, facial electromyography, as well as event-related potentials and auditory steady-state responses (ASSR) derived from electroencephalography. We conducted four experiments with a total of 95 participants, presenting three neutral sounds paired with either a pleasant odor, an unpleasant odor, or odorless air. The first experiment involved uninstructed participants and frequency-modulated conditioned stimuli (CS) for ASSR analysis. In the second experiment, we omitted the frequency modulation and startle probe. The third experiment included pre-experiment instruction on CS-US contingencies, while the fourth employed a delay conditioning paradigm in contrast to the other three experiments. Our results revealed differences between CS+ and CS- only in the fear-potentiated startle response in Experiment 3. No other effects were found. The minimal or absent learning effects observed across multiple peripheral and neural physiological measures may be attributed to the extra-thalamic nature of olfactory pathways and the subsequent difficulty in forming associations with auditory stimuli. •4 experiments exploring the neurophysiology of appetitive and aversive conditioning•Only the fear-potentiated startle in one of the experiments showed effective conditioning•Lack of conditioning may be related to difficulties in audio-olfactory associations